Business Incubator Development Model on Campus to Encourage the Growth of Young Entrepreneurs - Shanti Ike Wardani; Anna Widayani; Ika Rachmawati; Nunuk Latifah; Rani Arifah Normawati (Cita Konsultindo Research Center, 2023)
A college is a good place to learn entrepreneurship by providing innovation to build own business. The purpose of this study is to determine how the model in developing a business incubator that can encourage the growth of young entrepreneurs. The type of research used in this study is descriptive qualitative approach. Data collection techniques used books and literature studies processed by means of data reduction and then presented through descriptions to be informative. For the college, there are four recommended pilot models, namely the Green Energy Incubator Model/Eco-friendly Energy, Manufacturing Incubator Model, Creative Industry Incubator Model, and Agribusiness Incubator Model can be used for future development. From the research, business incubators has an important role for universities in encouraging student creativity and innovation in entrepreneurship field. Through this performance in universities, it can be seen in developing start-ups related to Tridharma as an example of community service.